Health education during prenatal care for the prevention and control of gestational hypertension: an experience report (Research, Society and Development, 2020)
This study aimed to report a health education action with hypertensive pregnant women monitored in prenatal care at a health unit, whose proposal was to mitigate the problems of gestational hypertension from an intervention aimed at changing habits. It is a descriptive study with a qualitative approach, of the experience report type, which used the Theory of Problematization as a basis from the implementation of the Arco de Maguerez, which is subdivided into five stages: observation of reality; survey of key points; theorization; hypothesis development; and, return to reality. The main results obtained in the study showed that many pregnant women still maintained harmful habits to their health, mainly linked to unbalanced food and physical inactivity, directly interfering in pressure changes. From the intervention performed, these women were sensitized about the importance of self-care for the safe maintenance of pregnancy, in addition to promoting autonomy and individual empowerment.